2012
DOI: 10.1590/s1677-54492012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Resultados do tratamento da Insuficiência Venosa Crônica grave com espuma de polidocanol guiada por ultrassom

Abstract: CONTEXTO: A insuficiência venosa crônica (IVC) em suas formas mais graves, com ulceração e lesões inflamatórias, associa-se a um tratamento cirúrgico convencional de difícil execução. A escleroterapia de veias tronculares com espuma de polidocanol é considerada uma alternativa terapêutica com resultados satisfatórios. OBJETIVO: Relatar os resultados da escleroterapia com espuma de polidocanol no tratamento de pacientes com IVC de membros inferiores com úlcera ativa. MÉTODOS: Em um período de 48 meses, 71 pacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
1
12
0
1
Order By: Relevance
“…With relation to patients with severe CVI, Silva et al 17 showed that ultrasound-guided foam sclerotherapy had a significant effect on patients. Ulcers healed in 84.2% of cases, with a mean healing time of 37 days.…”
Section: Discussionmentioning
confidence: 99%
“…With relation to patients with severe CVI, Silva et al 17 showed that ultrasound-guided foam sclerotherapy had a significant effect on patients. Ulcers healed in 84.2% of cases, with a mean healing time of 37 days.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcer healing rate, clinical improvement and of QL were similar 88,90 . Silva 91 identified healing of 84.2% of ulcers. Randomized studies report similar healing of ulcers with surgery, thermal ablation or UFS, with numerous casuistic 77,92,93 .…”
Section: Foam Sclerotherapy Resultsmentioning
confidence: 99%
“…Schooling is a fundamental element so that people can access and seek information Invest Educ Enferm. 2017; 35 (3) in general, in addition to providing a better understanding of the guidelines given by the health professional. Similar data were found in another study, where low level of schooling limited access to information, making it difficult to understand the diet, physical activity, medication dosage, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Among the chronic wounds we work with vascular wounds, venous ulcer (VU) and diabetic foot (DF) lesions, because they constitute a major public health problem, both in Brazil as in the world, with physiological, psychosocial and cultural repercussions. (2) Treatment involves several factors and may be difficult, due to the disease's own changes, such as associated comorbidities, advanced age, eczema and dermatosclerosis, (3) and the therapy is related to correction of the preexisting condition and use of local measures to occur. (4) Among the various coverage's used in the treatment are activated carbon, charcoal with silver salts for lesions with a large amount of exudate; hydrocolloids in small and medium lesions; antibiotics and collagenase.…”
Section: Introductionmentioning
confidence: 99%